Psychometric properties of Nursing Time Management Scale (NTMS), Arabic version - Raj'a Nayef Zyoud (BMC, 2023)
Abstract Despite the presence of numerous generic time management instruments, relatively few research articles have assessed the validity and reliability of time management skills specific for the nursing profession. This study aimed at developing and validating a time management scale for nurses. Method A self-administered questionnaire was administered to 715 nurses working in hospitals and clinics in the northern region of the West Bank, Palestine. The scale was examined through exploratory factor analysis, reliability measures, and correlations with other scales. Results The scale revealed a 3-factor structure 1) organization of nursing work 2) planning and goal setting and 3) coordination of nursing work. The scale demonstrated excellent psychometric properties. Conclusions The Nursing Time Management Scale (NTMS) is a valid and reliable measure that can be used in assessing time management skills of nurses and in evaluating interventions and training modules aiming at developing nurses' time management skills.